Gestão democrática nas escolas: a atuação dos diretores escolares e os desafios para sua consolidação na rede municipal de Natal/RN - Oliveira, Elane de (2013)
The democratic management is a challenge for education, on the one hand for its actualization needs a link between the government and the educational institution. From that, research aims to understand the main challenges faced by the school administration to consolidate the management of public schools in Natal/RN. Against this context the methodology used was multiple cases, qualitative approach in which respondent were manager (director, deputy director and coordinator) of the four municipal schools and two representatives of the Democratic Management Commission of a Government departament of Education, Natal/RN. The analysis was made by peers, between schools that had grade superior IDEB that average stipulated by the federal government and two that had grade lower and between managers and representatives of the Secretary. Were used techniques of categorization and content analysis of the speeches of respondents. Was note that managers understand the importance of the participation about whole community in the democratic management, however only one school highlighted means of attracting the parents against to the difficulty of representing these. The lack of knowledge about the democratic management is evident mainly in the pair of schools with lower IDEB. That schools with a lower IDEB adhere to this management as a way to meet rules. So unanimous, the broad role of director hampers knowledge about the legislation. About relationship of the Government department with managers, there are some contradictions between the understanding of the role of the coordinator by managers and representatives of the Government department. It was perceptible the no uniformity about a good relationship between managers and Government department. It was notable features of democratic management in all school units, well as the efforts of the Government department in this scope. However there are also undemocratic features that deserve further study